Auditory, Phonological, and Semantic Factors in the Recovery From Wernicke's Aphasia Poststroke: Predictive Value and Implications for Rehabilitation. (October 2019) - Robson, Holly; Griffiths, Timothy D.; Grube, Manon; Woollams, Anna M.
Background. Understanding the factors that influence language recovery in aphasia is important for improving prognosis and treatment. Chronic comprehension impairments in Wernicke's aphasia (WA) are associated with impairments in auditory and phonological processing, compounded by semantic and executive difficulties. This study investigated whether the recovery of auditory, phonological, semantic, or executive factors underpins the recovery from WA comprehension impairments by charting changes in the neuropsychological profile from the subacute to the chronic phase. Method. This study used a prospective, longitudinal observational design. Twelve WA participants with superior temporal lobe lesions were recruited 2 months post–stroke onset (2 MPO). Language comprehension was measured alongside a neuropsychological profile of auditory, phonological, and semantic processing and phonological short-term memory and nonverbal reasoning at 3 poststroke time points: 2.5, 5, and 9 MPO. Results . Language comprehension displayed a strong and consistent recovery between 2.5 and 9 MPO. Improvements were also seen for slow auditory temporal processing, phonological short-term memory, and semantic processing but not for rapid auditory temporal, spectrotemporal, and phonological processing. Despite their lack of improvement, rapid auditory temporal processing at 2.5 MPO and phonological processing at 5 MPO predicated comprehension outcomes at 9 MPO. Conclusions . These results indicate that recovery of language comprehension in WA can be predicted from fixed auditory processing in the subacute stage. This suggests that speech comprehension recovery in WA results from reorganization of the remaining language comprehension network to enable the residual speech signal to be processed more efficiently, rather than partial recovery of underlying auditory, phonological, or semantic processing abilities.